Primary lymphoma of the central nervous system: a clinical-pathological and immunohistochemical study of ten autopsy cases Linfoma primário do sistema nervoso central: estudo clínico-patológico e imuno-histoquímico de dez casos de necropsia - Henrique Costa; Marcello Franco; Myriam Dumas Hahn (Arquivos de Neuro-Psiquiatria)
CONTEXT: Primary central nervous system lymphomas (PCNSL) are a rare subgroup of lymphomas generally associated with HIV and EBV. OBJECTIVE: To study ten autopsy cases of PCNSL, to describe the neuropathological findings, to characterize the phenotype of the neoplastic cells, to detect EBV in the lesion and to compare the findings with the clinical and laboratory data of the patients. METHOD: The clinical, histological and immunohistochemical data of ten cases of PCNSL, eight cases from patients with AIDS, identified among 265 autopsies of these patients were analyzed. RESULTS: Seven patients were males and the mean age was 40.9 years. The most frequent symptomatology was focal neurologic deficit (70%). Six patients presented with only one lesion. Histologically, densely cellular and polymorphous neoplasms with angiocentrism were observed, in 90% of cases. An association with other diseases was observed in four cases. Most patients had diffuse large B cell non-Hodgkin’s lymphoma. EBV was detected by immunohistochemistry in only one case. The lack of detection of the virus might have been due to the long time of fixation of the brain which might have inactivate epitopes therefore compromising the testing. CONCLUSION: In the present series, PCNSL presented with focal symptoms, with unifocal or multifocal lesions, with a predominant B-cell CD20 positive phenotype, rarely associated with EBV. CONTEXTO: Linfoma primário do sistema nervoso central (LP-SNC) é raro subgrupo de linfomas relacionado à AIDS, geralmente associado EBV. OBJETIVO: Identificar os achados clínico-patológicos dos pacientes com LP-SNC. MÉTODO: Foram analisados dados clínicos, histológicos e imuno-histoquímicos de dez necrópsias de LP-SNC, oito deles de pacientes com AIDS, identificados entre 265 autopsias destes. RESULTADOS: Sete pacientes foram masculinos e a idade média foi 40,9 anos. A sintomatologia neurológica mais freqüente era focal (70%). Seis exibiram lesão única. Histologicamente, eram neoplasias densamente celulares e polimorfas, com angiocentrismo em 90% dos casos. Em quatro casos, houve associação com outras afecções. A maioria dos casos foi de linfoma não-Hodgkin difuso de grandes células B. A pesquisa para EBV foi positiva em um caso. CONCLUSÃO: Predominaram os LP-SNC associados à AIDS, com sintomatologia focal, lesão em massa ou multifocal, com predominância de células B CD-20.